Analysis of Factors That Influence in Using SIMVONI with UTAUT - Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo; Fajar Annas; Achmad Bias Firmansyah (Future Science, 2022)
The Covid-19 pandemic has hampered many sectors of life. But accelerating the coming of the future with the increasing use of IT in all sectors. One of the technologies adopted by SIMVONI in the midst of a pandemic is virtual tour technology which is implemented in museums which allows people to travel to museums virtually. The use of virtual tour technology is very useful during a pandemic or even after a pandemic because the reach of museum tourists is wider. This study uses the UTAUT model with several variables, namely Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition, Behavioral Intention to Use, Gender, and Age. The purpose of this analysis is to find out what factors are the user's interest in using SIMVONI as well as. In addition, the results of this research can be the basis for further development by the developer. The research was conducted by distributing questionnaires to 126 SIMVONI users and analyzed using the Structural Equation Model (SEM) method. The results of the SEM analysis show that several variables are factors that significantly affect the use of SIMVONI.